2020
DOI: 10.5194/adgeo-52-67-2020
|View full text |Cite
|
Sign up to set email alerts
|

Statistical moments of power spectrum: a fast tool for the classification of seismic events recorded on volcanoes

Abstract: Abstract. Spectral analysis has been applied to almost thousand seismic events recorded at Vesuvius volcano (Naples, southern Italy) in 2018 with the aim to test a new tool for a fast event classification. We computed two spectral parameters, central frequency and shape factor, from the spectral moments of order 0, 1, and 2, for each event at seven seismic stations taking the mean among the three components of ground motion. The analyzed events consist of volcano-tectonic earthquakes, low frequency events and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Although the automatic triggering procedure does not allow us to discriminate among the different types of events, it is interesting that it detected at least four periods of "anomalous seismicity" in late 2018, precisely October 22, 25-27, 30-31 and November 2, 4-6. To further investigate the overall signal properties, we compute the spectral parametrization of the whole dataset from 19 October to 13 November in terms of central frequency and shape factor of the power spectra (Kramer, 1996) for each node. The application of this methodology provides an effective image of the entire time record in a few seconds, as successfully applied in other volcanic settings (Galluzzo et al, 2020). In Figure 3, we plot spectral results for node 117 which shows an anomalous pattern similar to the one described above, both in terms of central frequency and shape factor of the spectra.…”
Section: Preliminary Data Inspection and Automatic Event Detectionmentioning
confidence: 84%
“…Although the automatic triggering procedure does not allow us to discriminate among the different types of events, it is interesting that it detected at least four periods of "anomalous seismicity" in late 2018, precisely October 22, 25-27, 30-31 and November 2, 4-6. To further investigate the overall signal properties, we compute the spectral parametrization of the whole dataset from 19 October to 13 November in terms of central frequency and shape factor of the power spectra (Kramer, 1996) for each node. The application of this methodology provides an effective image of the entire time record in a few seconds, as successfully applied in other volcanic settings (Galluzzo et al, 2020). In Figure 3, we plot spectral results for node 117 which shows an anomalous pattern similar to the one described above, both in terms of central frequency and shape factor of the spectra.…”
Section: Preliminary Data Inspection and Automatic Event Detectionmentioning
confidence: 84%
“…Finally, Power Spectral Density was calculated to check if characteristic periodicities exist for each site. The reliability and significance of the spectral peaks were proved by statistical and empirical methods (Godin, 1972). The authors found that most of the residual periodicities are related to ambient factors, while two specific cyclicality have a possible local endogenous origin.…”
Section: Contributions To the Special Volumementioning
confidence: 99%
“…In Galluzzo et al (2020), spectral analysis has been applied to almost thousand seismic events recorded at Mt. Vesuvius (Italy) in 2018 with the aim to test a new tool for a fast classification of seismic events.…”
Section: Contributions To the Special Volumementioning
confidence: 99%